2014
DOI: 10.1093/jac/dku181
|View full text |Cite
|
Sign up to set email alerts
|

Carbapenemase and virulence factors of Enterobacteriaceae in North Lebanon between 2008 and 2012: evolution via endemic spread of OXA-48

Abstract: Horizontal transfer of related plasmids has facilitated the spread of the bla(OXA-48) gene into several Enterobacteriaceae species, including virulent E. coli. Their clonal diversity and the presence of faecal carriers in the community suggest an endemic spread of OXA-48.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
57
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(58 citation statements)
references
References 35 publications
0
57
1
Order By: Relevance
“…pneumoniae in rural Cambodia in 2011 was still low, 1% in humans and not detected in livestock. Community carriage of bla OXA‐48 harbouring Enterobacteriaceae is rare, but has been reported from humans in Lebanon (Beyrouthy et al, ) and Switzerland (Zurfluh et al, ). Bla OXA‐48 harbouring isolates expressed a non‐wild‐type phenotype to meropenem, ciprofloxacin, sulfamethoxazole/trimethoprim, piperacillin/tazobactam, tetracycline and chloramphenicol but colistin resistance genes were not detected.…”
Section: Discussionmentioning
confidence: 99%
“…pneumoniae in rural Cambodia in 2011 was still low, 1% in humans and not detected in livestock. Community carriage of bla OXA‐48 harbouring Enterobacteriaceae is rare, but has been reported from humans in Lebanon (Beyrouthy et al, ) and Switzerland (Zurfluh et al, ). Bla OXA‐48 harbouring isolates expressed a non‐wild‐type phenotype to meropenem, ciprofloxacin, sulfamethoxazole/trimethoprim, piperacillin/tazobactam, tetracycline and chloramphenicol but colistin resistance genes were not detected.…”
Section: Discussionmentioning
confidence: 99%
“…A Jordanian study reported recently that MDR E.coli isolates from feces of infants accounted for 30.6%, and all were ESBL producers. [32]. In China, the prevalence of carbapenems-resistant among Enterobacteriaceae in the fecal flora of hospitalized patients was 6.6% (20/303 patients), of which 8 isolates were carried bla KPC-2 , bla IMP-4 and bla NDM-1 and typed as carbapenemase producers [33].…”
Section: Discussionmentioning
confidence: 99%
“…and [38][39][40][41]. More recently, the OXA-48-like variant OXA-244 was also identified in an ST38 E. coli isolated from a hospitalized patient in France without any travel history [42].…”
Section: E Coli St2914 Ctx-m-15mentioning
confidence: 95%